Staying involved "because the need seems so huge" : an exploration of the care processes used by midwives in their work with women living in areas of high deprivation : a grounded theory study : a thesis submitted in partial fulfilment of the requirements for the degree of Master of Arts in Midwifery, Massey University - Griffiths, Christine (Massey University, 2001)
It is estimated that 17-20 percent of New Zealand's population lives in relative poverty (National Health Committee, 1999; Waldegrave, King & Stuart, 1999). Poverty and ill health are closely related- 'with very few exceptions the financially worst off experience the highest rates of illness and premature death' (National Health Committee, 1998, p.8). Although much has been written about the impact of low socioeconomic status (SES) on pregnancy and birth outcomes, there is little written about the actual care midwives provide to childbearing women, especially to those living in socioeconomic deprivation. Grounded theory was the methodology used to explore the care provided by independent midwives to childbearing women, especially those of low SES. Through a process of theoretical sampling, independent midwives were interviewed about the care processes used in their work with women living in areas of high deprivation. Initial recruitment for the study was of midwives providing care to women living in thirteen selected meshblocks in a New Zealand city. Each of the meshblocks had been assigned a deprivation score based on the New Zealand Deprivation 1996 index showing them to be areas of high socioeconomic deprivation. Using the constant comparative method of data analysis, categories and properties were elicited which reflected the care processes used by midwives. These were used to develop a conceptual framework that fitted the collected data. The core category of 'Staying involved 'because the need seems so huge'' was the basic social process which emerged from the data. The midwives stayed involved throughout the woman's pregnancy and childbirth because the woman's need was so huge, to ensure an optimal pregnancy outcome for both the woman and her new baby. Four other categories were also identified; 'Forming relationships with the wary', 'Giving 'an awful lot of support'', 'Remaining close by' and 'Ensuring personal coping'. Details of the conceptual framework have relevance to the midwifery community, specifically to those midwives who work with women living in areas of high deprivation.
Keywords: Midwives, New Zealand; Poor women's health; Maternal health services